Supramolecular ultra-short dehydropeptide-based hydrogels as potential affordable nanocarriers - Veloso, Sérgio Rafael Silva (2021)
A library of Cbz-protected dehydrodipeptides was synthesised and evaluated as minimalist hydrogels. The molecular aggregation, self-assembly, gelation and biocompatibility were thoroughly studied through fluorescence spectroscopy, and the mechanical properties were assessed. The compounds that afforded hydrogels were evaluated as drug delivery systems for curcumin and doxorubicin using biomembrane models.